1991
DOI: 10.3109/00365529108996486
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Symptoms Suggestive of Esophageal Disorders

Abstract: A questionnaire study was conducted to assess the prevalence and severity of symptoms suggestive of esophageal disorders in a general population. The study included 407 randomly selected subjects, evenly distributed in terms of sex and age, within the age span of 20-79 years. A total of 337 subjects replied (85%). Symptoms suggestive of gastroesophageal reflux were found among 25% of the participants. Cough on swallowing was common (27%), as was globus (16%) and chest pain (13%). In addition, dysphagia was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
5
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 17 publications
5
114
5
2
Order By: Relevance
“…Previous epidemiological findings concerning the associations between smoking habit and GERD, FD, or IBS have been inconclusive (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Several studies have shown that smoking is significantly associated with GERD (10-13), uninvestigated dyspepsia (14-16), postprandial distress syndrome (a subtype of FD) (17,18), and IBS (19,20), especially, in female IBD (21) and diarrhea-predominant IBS (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous epidemiological findings concerning the associations between smoking habit and GERD, FD, or IBS have been inconclusive (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Several studies have shown that smoking is significantly associated with GERD (10-13), uninvestigated dyspepsia (14-16), postprandial distress syndrome (a subtype of FD) (17,18), and IBS (19,20), especially, in female IBD (21) and diarrhea-predominant IBS (22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physicians should pay attention to the overlapping of functional GI disorders. There are several studies concerning risk factors associated with GERD, FD, or IBS (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Our previous study showed that smoking and drinking habits were associated with GERD (13); female gender, low body mass index (BMI), smoking and drinking habits with FD (18); younger age, female gender, low BMI and presence of allergic diseases with IBS (22).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dysphagia in the general population is not well established, but several studies have suggested that between 7% and 10% of adults are affected. 11,12 Complaints about dysphagia appear to increase with age, but usually are not attributed to the ageing process itself. 13 Dysphagia is not uncommonly associated with oesophageal manometric findings which may be present with chest pain symptoms as well.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroesophageal reflux disease, one of the most prevalent health disorders in the Western world (7)(8)(9), is strongly associated with adenocarcinoma of the esophagus (5,(10)(11)(12), which stands in sharp contrast to the lack of association between reflux and squamous cell carcinoma of the esophagus (5,10). A link between gastroesophageal reflux and laryngeal and pharyngeal cancers has also been suggested, based on results from several case series (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%